2019
DOI: 10.1007/s00202-019-00761-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach in assessment of a ferroresonant circuit

Abstract: This paper presents possibilities offered by a diagnostic system called FeD. The system is completely original; it has been developed by the authors on the basis of Arduino platform. The system has been designed to perform and record measurements and to carry out different numerical operations. The real-time function for several operations is incorporated in this system. The necessary input data for the system consist of the electrical voltage waveforms only. Rescaled voltage quantities can be displayed, measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Fractional calculus has many other applicationsalso in other fields, like control systems [7]. In circuit theory some studies have shown its usefulness when modelling coils with ferromagnetic cores [8,9,10]. As for the elements of fractional calculus, there are many definitions of derivatives and integrals [11].…”
Section: Fractional Model Of Supercapacitormentioning
confidence: 99%
“…Fractional calculus has many other applicationsalso in other fields, like control systems [7]. In circuit theory some studies have shown its usefulness when modelling coils with ferromagnetic cores [8,9,10]. As for the elements of fractional calculus, there are many definitions of derivatives and integrals [11].…”
Section: Fractional Model Of Supercapacitormentioning
confidence: 99%
“…Through an adjustment of the source voltage level one can intentionally induce a ferroresonance phenomenon in the circuit. The FeD system [5] was used to acquire the voltages and current waveforms of all circuit components ( Fig. 1.…”
Section: Circuit Measurementsmentioning
confidence: 99%
“…During the measurements the ferromagnetic core coil has reached its saturation region conditions. The flux linkage, a quantity not measurable directly, was obtained on the basis of its definition as a time integral of the voltage across the coil [5].…”
Section: Circuit Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from classic examples like the modeling of viscoelastic materials [ 4 ] and the diffusion process [ 5 , 6 ], it was also found to be useful in economics for modeling of financial systems and economic growth [ 7 , 8 ], in medicine and biomedical engineering for disease analysis, drug modeling and administration, and signal acquisition [ 9 , 10 , 11 , 12 , 13 ], in computer science [ 14 ] for the development of neural networks with memory effects, and other applications with time-varying values of fractional-orders [ 15 ]. Only in the field of electrical engineering do some recent advances involve mathematical descriptions of supercapacitors [ 16 , 17 ], lithium-ion batteries with nonlinear capacities [ 18 ], and nonlinear coils in a ferroresonant circuit [ 19 ]. In control engineering, the algorithms of fractional-order controllers have received much interest, in particular, the fractional-order PID controller [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%